Test items of 3D printed copper alloy parts based on virtual reality technology. (15th July 2021) - Huo, Jiaofei; Zhang, Guangpeng
Abstract: Today, with the rapid development of virtual reality technology, 3D printing technology has gradually gained people's attention. Copper alloy parts have a wide range of uses in our lives, but due to the high technology required, production is more difficult. In order to make copper alloy parts more widely used, this paper uses 3D printing technology to print copper alloy parts, and through comparative experiments, the printed copper alloy parts are analyzed in detail. In the printing process, by adjusting the printing parameters, different parts are printed, and the printing results are analyzed for different parameters. The experimental results show that the experimental 3D printing technology can successfully print copper alloy parts. During the printing process, the input parameters have an extremely important effect on the results. The experimental results show that there are related parameters in the printing process, such as layer height, length, density, etc., which will cause deviations in the printing results. Among them, the layer height and length have the most important effect on the results, accounting for more than 50% of the deviation value. This shows that based on virtual reality technology, the use of 3D printing copper alloy parts is achievable.